Using An Analytical Method for Solving a Type of Differential - Difference Equations - Safa Issam Ahmed; Muayyad Mahmood Khalil; Nihad Shareef Khalaf (Genius Journals, 2022)
Laplace decomposition method is predicated on Laplace transform method and Adomian decomposition method. through this paper we show that the technique is applicable to certain successive interval valued linear in addition as nonlinear differential-difference equations of order (1, 2), which means the differential is of order one and the difference order is two. it's also shown that the method gives exact solution for linear problems and suitable approximate solution for nonlinear problems. Three problems are selected to show the applicability of the method.
Keywords: Differential; equation; decomposition; transform